Elaboración de un plan de mantenimiento preventivo en motobombas centrífugas de agua para piscinas - Martínez Callejas, Javier Alejandro (Universidad Antonio Nariño, 2021)
In the present research work, the creation of a preventive maintenance plan in centrifugal water pumps for swimming pools is proposed, for this, a study of bibliographic references was necessary to lay the foundations of the subject in question and henceforth, carry out an analysis on the importance of preventive maintenance in this type of machines for domestic use. Thus, it is possible to affirm that the first link for the proposal of a plan in this matter, starts from a visual, auditory, vibration diagnosis, helping the above to determine a list of supplies, tools and their characteristics that help to calculate an estimate of the cost of preventive maintenance on the equipment on an annual basis.